Civic Education at School in Postdemocracy (Case Study – Bulgaria) - Tsakova, Ivka; Stoeva, Ivajla (Research Papers, 2018)
We scrutinize the civic education at school using the broad theoretical framework of the global neoliberal capitalism that determines the common background of the contemporary world. The time we are living can be characterized by three crises: crisis of the liberal democracy, crisis of the national state and crisis of the American world hegemony.Our main goal is to show the existing serious deficits of civic education and upbringing of pupils in the national states members of the European Union (using as case study Bulgaria) operating in neoliberal capitalism and postdemocracy at the beginning of XXI century, as well as proposing ways to overcome the existing democratic deficit.We will achieve this goal by answering the following research questions: a) Explaining basic concepts (democracy, capitalism, neoliberalism, civic education, etc.); b) Drafting an exemplary portrait of the good citizen of the national state member of the EU; c) Disclosing actual accents (reforms) in the sphere of civic education in France, Germany and the EU as a whole; d) Studying the Bulgarian state educational standards for civic education, accompanied with conclusions about their implementation; e) Suggestions for making up for basic pedagogic and democratic deficiencies towards the Bulgarian state (educational) institutions.The paper is predominantly based on the critical method, elaborated by the critical social and political theory (Colin Crouch, Wendy Brawn). The critical approach allows us to take side in order to protect the collective and democratic values endangered by the dominating neoliberal market rationality and over individualism. The critical reflex allows us explain the concept „good citizen“, differentiating it from the self-sufficient homo economicus.Binding both concepts civic education and postdemocracy has never been done before in Bulgaria. This paper is a bold attempt to situate the civic education issue of the Bulgarian young people at the XXI century in times of democratic crisis along with the following challenges.
Keywords: Civic education; Good citizen; Neoliberal capitalism; Postdemocracy